The whistling season - Doig, Ivan (Harcourt, 2006)
Hired as a housekeeper to work on the early 1900s Montana homestead of widower Oliver Milliron, the irreverent Rose and her brother, Morris, endeavor to educate the widower's sons while witnessing local efforts on a massive irrigation project.